Assessment of Fixation of Mandibular Interforaminal Fractures by Using a Single Second-Generation Headless Compression Screw: A Pilot Study. Issue 2 (June 2017) - Ram, Rangila; Ahsan, Razi; Bhardwaj, Yogesh; Ghezta, Narotam; Kumar, Santosh
The aim of this article is to evaluate the efficacy of a single second-generation headless compression screw along with a lower arch bar in the fixation of interforaminal mandible fractures. A total of seven patients were included in the study. An open approach was used either intraorally or extraorally. A second-generation 3.0 HCS (headless compression screw), 24 to 32 mm in length, diameter at the head of 3.5 mm, smooth shaft with 2.0 mm and at the leading edge 3.0 mm (Synthes, Paoli, PA) was used for the fixation along with a lower arch bar. Postoperative clinical and radiographic follow-up was performed at 3 weeks, 3 months, 6 months, and 1 year. A single, cannulated HCS was found to be effective in fixation of interforaminal mandible fractures except in one case where a miniplate had to be applied subapically. Clinical and radiographic follow-up revealed accurate reduction and fixation in all cases and no postoperative occlusal disturbances. A single, second-generation HCS along with a lower arch bar provides good results when used for the fixation of interforaminal mandible fractures. Headless compression screw fixation of interforaminal mandible fracture is a simple, quick, economic, and efficient method of rigid fixation with minimum complications.